ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI DAGING AYAM BROILER DI PASAR CIBINONG KABUPATEN BOGOR - Ramadhanti, Sarah Faradhila; Handayani, Migie; Mukson, Mukson (Universitas Galuh, 2023)
Many people consume broiler chicken meat because it is a type of animal protein source. In order to investigate the factors influencing consumer decisions to purchase broiler carcass meat at Pasar Cibinong in Bogor Regency, this study set out to identify the characteristics of consumers of broiler carcass meat. A case study methodology and an accidental sampling technique are both used in this sort of research on 210 housewives who are purchasing chicken at Pasar Cibinong. Methods of data analysis using descriptive analysis and multiple logistic regression analysis of binary. The number of family members, family income, education level, price, location, and quality are the independent variables in this study. The dependent variable in this study is the consumer's decision to purchase broiler chickens. The findings demonstrated that a number of variables, including family size, income, level of education, cost, and location, simultaneously had a significant impact on consumers' decisions to buy broiler chicken at Pasar Cibinong. Broiler chicken purchase decisions in Pasar Cibinong are significantly influenced by the variable number of family members, price, and location.